امام علی علیه السلام میان شجاعت و عقل - مطالعه تحليلى" - Morahhej Rebat, Majed (Journal of College of Education, 2022)
Abstract: Imam Ali (pbuh) gave great dimensions in courage and wisdom until, if necessary, he became a universal example of having courage, reason and wisdom, and Imam Ali (pbuh) combined courage and dream, and these characteristics are familiar to men. is not. He did not dare to destroy the mind and in many wars he rules this mind and has chastity of spirit and forgives others on the battlefields. His character appeared in dreams and courage, he was the king of patience and restrained himself from whims and desires. He was generous in forgiving and forgiving. Courage is a gift that the great God men enjoy, Imam Ali (as) is one of them and the Arabs have inherited courage since pre-Islamic times, the reason for this is that their living conditions in the degree The difficulty was high. They consider eating with the edge of the sword and not with effort and fatigue to be the characteristics of men. The fact is that this phenomenon is considered as the blame of the Arabs of ignorance, and the Arabs consider their many conquests in ignorance as a source of pride for them and intimidation of their enemies so that they do not get involved in their conquest. The Arabs remained fearless after arming their land and honor with religion and jihad to defend their religion. Courage is the power of faith before the power of the body, and courage is responsibility and defending the religion of Islam and defending the saints of God, and courage is good opinion and cooperation against the enemy if necessary, and appears and is strengthened according to the circumstances of the brave old man. And that some situations caused by the mind turn anger into patience, even blood is preserved among humanity, and this phenomenon is reflected in the image of Imam Ali (as).